2020
DOI: 10.3390/medicina56110564
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Efficacy of Variable-Thread Tapered Implants—A Retrospective, Clinical and Radiological Evaluation

Abstract: Background and Objective: There is multifaceted evidence that variable-thread tapered implants (VTTIs) offer high primary stability but few regarding the long-term success. This retrospective clinical and radiological cohort study assessed the long-term outcome of VTTIs. Material and Methods: All patients treated in an OMFS practice with NobelActive Internal® VTTI between October 2007 and September 2011 were invited for clinical examination. The outcome variables were (i) survival rate, (ii) implant success ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…The VTTIs have been broadly applied in clinical practice, particularly in anterior aesthetic areas, edentulous jaws, and poor bone quality regions. Some retrospective studies have confirmed its great clinical performance (Blume et al, 2020;Ho et al, 2013;Kielbassa et al, 2009), but the research for survival rates based on large population is infrequent. To the best of our knowledge, this is also the first study to report risk factors related to implant loss of VTTIs in such a sample.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The VTTIs have been broadly applied in clinical practice, particularly in anterior aesthetic areas, edentulous jaws, and poor bone quality regions. Some retrospective studies have confirmed its great clinical performance (Blume et al, 2020;Ho et al, 2013;Kielbassa et al, 2009), but the research for survival rates based on large population is infrequent. To the best of our knowledge, this is also the first study to report risk factors related to implant loss of VTTIs in such a sample.…”
Section: Discussionmentioning
confidence: 99%
“…Also, Takamoli et al (2021) found that over 80% of implant losses occurred after the connection of restorations through an 8.2-year retrospective study with 710 implants. Few studies evaluated the early and late survival rate of this VTTI system, and only two follow-up surveys found slightly high ratios in early implant loss (Blume et al, 2020;Saridakis et al, 2018). The sample was small in the above studies, thus, the proportional relationship TA B L E 2 Life table analysis of VTTIs at the implant and patient levels.…”
Section: Ta B L E 1 (Continued)mentioning
confidence: 99%
See 2 more Smart Citations
“…Oral implants are widely used as a highly predictable prosthetic treatment for partially and fully edentulous patients, and in most cases successful long-term functional and esthetic outcomes can be expected [1][2][3][4][5]. Two types of complication can occur after implant treatment: biological and mechanical [6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%